2018
DOI: 10.1016/j.tics.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting and Utilising Intersubject Variability in Brain Function

Abstract: We consider between-subject variance in brain function as data rather than noise. We describe variability as a natural output of a noisy plastic system (the brain) where each subject embodies a particular parameterisation of that system. In this context, variability becomes an opportunity to: (i) better characterise typical versus atypical brain functions; (ii) reveal the different cognitive strategies and processing networks that can sustain similar tasks; and (iii) predict recovery capacity after brain damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
202
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(207 citation statements)
references
References 138 publications
(199 reference statements)
5
202
0
Order By: Relevance
“…Indeed, dietary intake of ω-3 PUFAs represent a primary source of individual differences in nutritional status (Ervin, Wright, Wang, & Kennedy-Stephenson, 2004). Moreover, individuals exhibit sizeable inter-individual differences in brain structure and function, which are closely linked to cognitive and behavioral traits (Seghier & Price, 2018). The present study therefore investigated whether plasma biomarkers of ω-3…”
mentioning
confidence: 98%
“…Indeed, dietary intake of ω-3 PUFAs represent a primary source of individual differences in nutritional status (Ervin, Wright, Wang, & Kennedy-Stephenson, 2004). Moreover, individuals exhibit sizeable inter-individual differences in brain structure and function, which are closely linked to cognitive and behavioral traits (Seghier & Price, 2018). The present study therefore investigated whether plasma biomarkers of ω-3…”
mentioning
confidence: 98%
“…There are a number of studies which have assessed this for cerebral cortical activity (Kherif, Josse, Seghier, & Price, 2009;Miller, Donovan, Bennett, Aminoff, & Mayer, 2012;Seghier & Price, 2016;Seghier & Price, 2018). This has the additional advantage that intersubject variability can be determined.…”
mentioning
confidence: 99%
“…This has the additional advantage that intersubject variability can be determined. There are a number of studies which have assessed this for cerebral cortical activity (Kherif, Josse, Seghier, & Price, 2009;Miller, Donovan, Bennett, Aminoff, & Mayer, 2012;Seghier & Price, 2016;Seghier & Price, 2018). For example, Miller et al (2012) found that patterns of fMRI activation in the cerebral cortex during a memory retrieval task differed between individual subjects from the pattern of activity derived from group analysiswhich was attributed to variation in cognitive processing and encoding style.…”
mentioning
confidence: 99%
“…While variability is typically treated as a nuisance or noise factor in neuroscience, proper understanding of a phenomenon requires scrutiny of both the group mean and its natural variation (79,80). (This is clearly illustrated by the HPC maps of Fig.…”
Section: Functional Implicationsmentioning
confidence: 99%